Adaptasi Alat Ukur Dukacita untuk Remaja Indonesia dengan Keluarga yang Meninggal Mendadak - Prudentia Kirana Gunawan; Hendriati Agustiani; Laila Qodariah (JKI (Jurnal Konseling Indonesia), 2021)
An abnormal form of grief, prolonged grief disorder (PGD), most common cause are sudden deaths of immediate family members. The latest and most developed assessment of prolonged grief disorder (PGD) is the PG-13; available in adult and child form. This research adapts PG-13 children form to the appropriate context of Indonesian adolescence. As supplementary, adaptation was also done on the People Places and Things You Miss Inventory (PPTIM). Adaptation process follows the steps of adaptation proposed by Beaton D. E. This process focuses on the appropriateness of language, maintenance of the content, also the understandability and practicality of the adapted self-report measure through pretesting process. Pretesting was done on 46 adolescence that has lost an immediate family member due to sudden death. Cause of death are not limited as long as it is sudden; time of death is limited however to minimal of 6 months prior pretesting.